Platform for wireless pressure sensing with built-in battery and instant visualization. (August 2019) - Cheong, Woon Hyung; Oh, Byungkook; Kim, Se-Hee; Jang, Jiuk; Ji, Sangyoon; Lee, Seunghee; Cheon, Jinwoo; Yoo, Seunghyup; Lee, Sang-Young; Park, Jang-Ung
Abstract: Wireless communication through linkage with a smartphone and other portable devices in the sensor area are essential for increasing the efficiency of utilization by storing sensing-value data. Thus, the demand for wireless technology is increasing due to the advantages it provides for the various applications that use these data. However, there is still considerable ambiguity concerning the low portability of such technology due to the increased volume with component integration, the high consumption of power, and the necessity of having a separate battery. Herein, we present solutions for these problems with demonstrations that involve 1) the miniaturization of the device by altering the structure of the built-in battery, 2) the use of a pressure-activated switch for the low-power driving technology, and 3) the implementation of a wireless communication platform by integrating a Bluetooth module with the devices. In addition, we demonstrate a human-interactive display that enables users to instantly observe the changes in the brightness of the organic light-emitting diodes (OLED) as the pressure changes. We show that the system can display the measured, real-time pressure values on the screens of mobile devices, which represents a significant advancement in the fields of energy science and biomedical science. Graphical abstract: Image 1 Highlights: Integrated system of portable pressure measuring device is developed. The built-in structure of the battery present high portability and the switch enables long-term operation. The device is capable of wireless communication with smartphones in real-time.